2015
DOI: 10.2147/ijn.s77867
|View full text |Cite
|
Sign up to set email alerts
|

Functional consequences for primary human alveolar macrophages following treatment with long, but not short, multiwalled carbon nanotubes

Abstract: Purpose: Multiwalled carbon nanotubes (MWCNTs) are a potential human health hazard, primarily via inhalation. In the lung, alveolar macrophages (AMs) provide the first line of immune cellular defense against inhaled materials. We hypothesized that, 1 and 5 days after treating AMs with short (0.6 μm in length; MWCNT-0.6 μm) and long (20 μm in length; MWCNT-20 μm) MWCNTs for 24 hours, AMs would exhibit increased markers of adverse bioreactivity (cytokine release and reactive oxygen species generation) while also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…Cell migration is a crucial step in many physiological or pathological processes such as wound-healing, cancer, and inflammation [ 22 ]. It is reported that long MWCNT (20 μ m) reduced the migratory capacity in primary human alveolar macrophages (AMs) along with increased expression of MARCO [ 23 ]. In contrast, MWCNT promoted cell migration in RAW263.7 macrophage cell lines and human microvascular endothelial cells (HMVEC) [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cell migration is a crucial step in many physiological or pathological processes such as wound-healing, cancer, and inflammation [ 22 ]. It is reported that long MWCNT (20 μ m) reduced the migratory capacity in primary human alveolar macrophages (AMs) along with increased expression of MARCO [ 23 ]. In contrast, MWCNT promoted cell migration in RAW263.7 macrophage cell lines and human microvascular endothelial cells (HMVEC) [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…One in vitro study investigated the potential pathophysiological consequences of primary human alveolar macrophages exposed to long MWCNTs (20 μm in length) and short MWCNTs (0.6 μm in length). After a 24-hour treatment with long MWCNTs, alveolar macrophage viability decreased, superoxide levels increased, and inflammatory mediator release increased, and phagocytosis and migratory capacity of alveolar macrophages decreased [ 96 ]. In addition to causing cytotoxicity, pristine MWCNTs and functionalized MWCNTs with COOH and PEG reportedly induce significant production of inflammatory cytokines, including TNF-α, IL-1β and IL-6, at different concentrations from 25 to 200 μg/ml [ 97 ].…”
Section: Main Textmentioning
confidence: 99%
“…Further studies should be conducted to investigate the direct relationship between CNT phagocytosis, oxidative stress and their impact on the release of IL-1β, for example by using endocytosis inhibitors. Moreover, frustrated phagocytosis also led to CNT biopersistence, as the clearance of inhaled material is hampered, and to the release of pro-inflammatory (IL-6 and IL-8) and pro-fibrotic mediators (TGF-β) [ 58 , 59 ]. These data suggest a relevant role of oxidative stress in CNT-induced IL-1β release and fibrosis development.…”
Section: Indirect Effects Of Cnt On Fibroblastsmentioning
confidence: 99%
“…; length 20–50 μm and diameter 50 nm) stimulated the release of TGF-β in vivo, as measured by immunohistochemistry, contrary to short CNT (length 0.5-2 μm and diameter 50 nm). Long MWCNT (10 μg/ml; length 20 μm), but not short fibers (length 0.6 μm), were also shown to affect alveolar macrophage function, including cell death, ROS generation and pro-inflammatory (IL-6 and IL-8) mediator release [ 58 ]. A stronger ROS generation was also observed in A549 epithelial cells exposed to long CNT (length 5–30 μm; doses 5–20 μg/ml) compared to short fiber (length 0.5–2 μm) [ 76 ].…”
Section: Determinants Of the Fibrotic Activities Of Cntmentioning
confidence: 99%